Recurrent PRDM10 Fusions in Superficial CD34-Positive Fibroblastic Tumors : A Clinicopathologic and Molecular Study of 10 Additional Cases of an Emerging Novel Entity. Issue 4 (22nd February 2023) - Zhao, Ming; Yin, Xiaona; He, Huiying; Fan, Yuqian; Ru, Guoqing; Meng, Xuli
Abstract: Objectives: Superficial CD34-positive fibroblastic tumor (SCD34FT) is a rare mesenchymal neoplasm. The genetic alterations of SCD34FT have yet to be determined. Recent studies suggest it overlaps with PRDM10- rearranged soft tissue tumor ( PRDM10- STT). Methods: This study aimed to characterize a series of 10 cases of SCD34FT using fluorescence in situ hybridization (FISH) and targeted next-generation sequencing (NGS). Results: The study recruited 7 men and 3 women aged between 26 and 64 years. The tumors were located in the superficial soft tissues of the thigh (8 cases), foot, and back (1 case each), ranging in size from 1.5 to 7 cm. The tumors were composed of sheets and fascicles of plump spindled to polygonal cells, with glassy cytoplasm and pleomorphic nuclei. Mitotic activity was absent or low. Common and uncommon stromal findings included foamy histiocytic infiltrates, myxoid changes, peripheral lymphoid aggregates, large ectatic vessels, arborizing capillary vasculature, and hemosiderin deposition. All tumors expressed CD34, and 4 demonstrated focal cytokeratin immunoexpression. In 7 of 9 (77.8%) cases analyzed, FISH identified PRDM10 rearrangement. Targeted NGS revealed a MED12 :: PRDM10 fusion in 4 of 7 cases tested. Follow-up showed no recurrence or metastasis. Conclusions: We demonstrate recurrent PRDM10 rearrangements in SCD34FT and provide additional evidence of a close relationship to PRDM10- STT.